Relationship between emotional intelligence and benevolent leadership and its effect towards organisational citizenship behaviours mediated by organisational commitment - Tan, Jue Xin (2015)
The purpose of this study is to examine emotional intelligence as the antecedent of benevolent leadership and the relationship between benevolent leadership and organisational citizenship behaviours with organisational commitment as a mediator. This research intends to affirm the importance and effectiveness of benevolent leaders in improving the turnover issues in hotel industry of Malaysia and encourage employees to make extra contribution willingly. As benevolent leadership was mostly investigated by scholars in Chinese context, this is one of the pioneer researches to study benevolent leadership in a multicultural context. This study extends the body of knowledge of benevolent leadership as there were limited researches being done in examining its antecedent. Social exchange theory and path-goal theory were applied in supporting the proposed relationships and a total of seven hypotheses were proposed. The quantitative method is used in analyzing the data collected through questionnaires. Multistage sampling method was applied in the selection of respondents. There were 163 employees and 104 supervisors from four- or five-star hotels in Klang Valley participated in the questionnaire survey. The data screening was carried out to eliminate missing values and outliers in the data collected. The reliability and validity tests, multivariate assumption tests, and descriptive data analysis were conducted as well. Structural equation modelling was employed to analyze the data and test the hypotheses in this study. The result of this study shows that four out of seven hypotheses were supported. The findings have shown that emotional intelligence has no significant relationships with benevolent leadership, organisational commitment and organisational citizenship behaviours. Benevolent leadership is found to be the predictor employee’s citizenship behaviours mediated by employee’s commitment. There is a full mediation effect of organisational commitment towards the relationship between benevolent leadership and organisational citizenship behaviours. Limitations of the study and directions for future research are suggested in the last chapter.